Cholera outbreak in an informal settlement at Shahpur huts, Panchkula District, Haryana State, India, 2019 - Abhishek Jain; Sushma Choudhary; Ekta Saroha; Pankaj Bhatnagar; Pauline Harvey (Wolters Kluwer Medknow Publications, 2021)
In September 2019, after a reported death due to acute diarrheal disease in Shahpur village, Panchkula district, Haryana state, India, we conducted an outbreak investigation to identify the etiological agent, estimate the burden of disease, and make recommendations to prevent future outbreaks. The suspected cholera case was a resident of Shahpur huts, ≥1 year of age having ≥3 loose stools within a 24-h period between September 1 and 28, 2019 and a laboratory-confirmed cholera case, whose stool specimen tested positive for Vibrio cholerae. We identified 196 suspected cholera cases with a median age of 18 years (range: 1-65 years); 54% (106) being female. The overall attack rate was 8% (196/2,602), and the case fatality rate was 1% (2/196). Tested samples of water from tanks (n = 6), sewage effluent (n = 2), and 22% (4/18) of stool specimens collected from suspected cases were positive for V. cholerae. Strengthening surveillance, improving water, and sanitation systems are recommended to prevent future cholera outbreaks.